THE ROLE OF PHYSICAL EDUCATION IN IMPROVING THE EFFECTIVENESS OF LESSONS IN GENERAL EDUCATION SCHOOLS - Abdusalomov Abdusattor Habibullo ugli; Tillyakhodjaev Azizkhan Alokhonovich (Scholars Digest Publishing, 2023)
This article explores the role of physical education in improving the effectiveness of training in secondary schools. It discusses the advantages of physical education, methods of its inclusion in school curricula and positive results in academic Jismoniy tarbiyarformance. The article ends with teachers and politicians making suggestions for the further development of physical education in schools.
Keywords: physical education, secondary schools, academic indicators, curriculum, benefits.